Cinderella's festive fake date - Baine, Karin (Harlequin romance, 2024)
Pottery studio owner Evie isn't feeling festive. Her ex-boyfriend - now her stepsister's fiance - is joining her family for the holidays. Going alone is not an option, but Evie's afraid of being hurt again. So, she hopes an online fake dating service can work some magic. Guarded workaholic Jake requires a plus-one for his mother's nuptials, and enticing Evie fits the bill. Over steaming hot chocolate, they agree to a romance ruse. Only their undeniable attraction soon has them stealing kisses under the mistletoe. And they discover there's thin ice between faking it and truly falling!